Karakteristik Fermentasi Rumen In vitro dengan Penambahan Sabun Kalsium Minyak Nabati pada Buffer yang Berbeda - S Suharti; D N Aliyah; S Suryahadi (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2018)
Canola oil and flaxseed oil are vegetable oils as potential sources of unsaturated fatty acid that could improve the production and quality of beef meat. However, the use of vegetable oils need to be protected to avoid biohydrogenation by rumen bacteria. The research was aimed to analyse effect of flaxseed/canola oils calcium soap in the different buffer media on in vitro fermentation characteristic. The experiment was conducted in a factorial randomized block design with 2 factors and 3 blocks based on rumen sampling time. The first factor was sources of vegetable oils (canola and falxseed) and the second factor was type of buffer (Kajikawa and McDougall). Variables observed were pH value, N-NH3 concentration, total volatile fatty acid (VFA), dry matter and organic matter digestibility. Data obtained was analysed using Analysis of Variance and any significant different further tested using Duncan Multiple Range Test. The results showed that there was no interaction between sources of diet and buffer. Supplementation of canola and flaxseed oils protected by calcium soap at level 6% did not affect pH value, dry matter digestibility, rumen protozoa and total bacteria. The use of different buffers affected pH value, dry matter digestibility, rumen protozoa and total bacteria. It’s concluded that the used of flaxseed oil or canola oil calcium soap did not alter rumen fermentation and McDougall buffer could improve in vitro fermentation activity compare to Kajikawa buffer. Keywords: biohydrogenation, calcium soap, canola oil, flaxseed oil, rumen fermentation